Biomechanical responses to landing strategies of female artistic gymnasts. Issue 11 (2nd November 2022) - Straker, Rebecca; Exell, Timothy A.; Farana, Roman; Hamill, Joseph; Irwin, Gareth
ABSTRACT: Inconsistencies between sexes in the landing criteria provided by the international gymnastics governing body (FIG) may predispose female gymnasts to lower extremity injury. This study aimed to investigate lower extremity biomechanics when performing the male and female landing strategy. Seven collegiate, female gymnasts (age: 20.5 ± 1.2 years, height: 1.64 ± 0.06 m, mass: 60.4 ± 10.2 kg) performed drop landings using the prescribed women's and men's landing strategy. Kinematic and kinetic data from 10 trials of each landing strategy were collected. Differences between landing strategy at individual and group level for key injury risk variables of the lower limb were explored. Group differences ( p ≤ .05) were reported in the sagittal range of motion (ROM) at the knees and hips, with the men's landing strategy eliciting a larger ROM decelerating the body upon impact. Large inter and intra-individual variation was apparent with different movement responses shown across individuals and demonstrating degeneracy as gymnasts satisfied the overall landing objective. These results indicate an individually favoured landing strategy to fulfil the informational constraints and hence supporting the use of a single-subject design. The current study emphasises the potential injury risk associated with the different informational constraints placed on females' landing strategy by the FIG, whilst recognising the individual gymnasts' task response. Highlights An increase in the range of motion at the knee and hip may support the recommendation of the men's landing style. Gymnasts appear to utilise individual landing strategies to complete the landing objective, supporting the use of a single-subject design.